Fat Politics Photography: The Stareable Body and “Openings” for Social Justice - Hladki, Janice (InTensions, 2016)
In complicating understandings of art’s effects, critical theorists mobilize the notion of “openings” to surface simultaneously the unpredictability and indeterminacy of ethical engagement as well as its possibility. I explore the potential of these ideas and consider their application through Haley Morris-Cafiero’s photography on fatness and disability in her Wait Watchers series. Through problematizing surveillance and staring relations, between the observed Fat woman and her watchers, and interrogating the constitution of the monstrous other, the photography unsettles regimes of normalization in relation to fatness and disability. The images invite recognition for embodied difference as they register the complexity and difficulty of social justice “openings” for anomalous embodiment.